(Se) socialiser par l’entretien - Guillaume Teillet (Terrains/Théories)
Based on an ethnographic investigation conducted from October 2014 to November 2017 in an open educational unit (UEMO) of the Judicial Protection of Youth (PJJ), this article shows in three distinct steps the way in which the socio-judicial interview produces social insofar as it is socialising and contributes to the manufacture of social futures. The analysis of the features of this state form of regulation of juvenile behaviour precedes the examination of the mode of socialisation to which it is linked. This aims to transform the body and emotions of individuals, their family relationships and their relationship to the written word, to authority and to institutions. The judicial scenes observed are then looked at as unequal confrontations between the judicial framework and the young people prosecuted, according to their primary socialisation and their life contexts, variations at the origin of the differentiation of their judicial paths... and of their social position.